2012
DOI: 10.1111/imb.12005
|View full text |Cite
|
Sign up to set email alerts
|

Targeting gene expression to the female larval fat body of transgenic Aedes aegypti mosquitoes

Abstract: As the fat body is a critical tissue for mosquito development, metamorphosis, immune and reproductive system function, characterization of regulatory modules targeting gene expression to the female mosquito fat body at distinct life stages is much needed for multiple, varied strategies for controlling vector-borne diseases such as dengue and malaria. The hexameric storage protein, Hexamerin-1.2, of the mosquito, Aedes atropalpus, is female-specific and uniquely expressed in the fat body of fourth-instar larvae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 86 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…In Aedes aegypti , a number of regulatory elements able to drive gene expression in specific tissues have been identified through transgenesis. These include the midgut 23 24 , the eye 25 , salivary glands 26 27 , testis 28 , fat body 29 30 31 , female flight muscle 32 , and ubiquitous expression 33 34 . Several regulatory elements have also been identified that drive expression in the female germline.…”
mentioning
confidence: 99%
“…In Aedes aegypti , a number of regulatory elements able to drive gene expression in specific tissues have been identified through transgenesis. These include the midgut 23 24 , the eye 25 , salivary glands 26 27 , testis 28 , fat body 29 30 31 , female flight muscle 32 , and ubiquitous expression 33 34 . Several regulatory elements have also been identified that drive expression in the female germline.…”
mentioning
confidence: 99%
“…Hexamerin-encoding transcripts corresponding to contig 1221 were found highly accumulated in both larvae and adults. Hexamerins expressed in adult mosquitoes have been reported [47] but their function during this developmental stage is unknown. Abundant larval mRNAs encoding ribosomal proteins, translation initiation factors and elongation factors represent the active protein synthesis machinery, consistent with the rapid growth rate during the third and fourth instars of mosquito larvae.…”
Section: Resultsmentioning
confidence: 99%